2017
DOI: 10.1002/pon.4442
|View full text |Cite
|
Sign up to set email alerts
|

Patient and caregiver perspectives on decision support for symptom and quality of life management during cancer treatment: Implications for eHealth

Abstract: Patients were faced with an overwhelming amount of information and relied on their caregivers to help navigate the complexities of cancer care and self-manage SQL. Health technologies can provide informational support; however, decision support needs to span multiple venues to avoid increasing disparities caused by a digital divide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 32 publications
1
54
0
1
Order By: Relevance
“…Throughout the literature review, ndings were that eHealth applications generated multiple arenas for communication on patients' and families' own terms, and in their own time. In all the included studies, patients' experiences were predominantly positive for eHealth applications and communication (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Eleven studies described patients' practical experiences of using various technological tools to communicate digitally with their caregivers (32,33,(35)(36)(37)(38)(39)(40)(41)(42)(43).…”
Section: E-health Applications -Promoting Communication On Patients' mentioning
confidence: 99%
See 2 more Smart Citations
“…Throughout the literature review, ndings were that eHealth applications generated multiple arenas for communication on patients' and families' own terms, and in their own time. In all the included studies, patients' experiences were predominantly positive for eHealth applications and communication (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Eleven studies described patients' practical experiences of using various technological tools to communicate digitally with their caregivers (32,33,(35)(36)(37)(38)(39)(40)(41)(42)(43).…”
Section: E-health Applications -Promoting Communication On Patients' mentioning
confidence: 99%
“…Eleven studies described patients' practical experiences of using various technological tools to communicate digitally with their caregivers (32,33,(35)(36)(37)(38)(39)(40)(41)(42)(43). In the twelfth study, patients described wanting technical communication aids both to receive and to provide information digitally, and thus facilitate communication with healthcare professionals (34).…”
Section: E-health Applications -Promoting Communication On Patients' mentioning
confidence: 99%
See 1 more Smart Citation
“…Wu and colleagues 19 explored the use of patient reported outcomes at 10 EPIC installation sites and found that while clinician prompts and alerts were automated, patient interventions were delivered after clinician synthesis of the information and ordering of patient education and referrals.Earlier work, with assessment plus tailored and automated self-care educational interventions, has been conducted in cancer care settings with positive results 10,19,20. Regular assessment or screening for cancer symptoms plus alerts to clinicians has been demonstrated to better sustain quality of life than usual care monitoring in patients with metastatic cancer13 but has not been shown to reduce specific symptomatology.Patient and caregiver focus groups conducted at the same institutions by Cooley et al (this issue-part I) resulted in findings aligned with the clinician focus groups 21. Issues surrounding contacting clinicians were relevant in both analyses, underscoring the importance of decision support systems to include clear instructions regarding patientprovider communication.…”
mentioning
confidence: 65%
“…The first pile consisted of articles ( n = 25) whose findings did not have the potential to be relevant for communication training. The four main reasons for not considering these articles were as follows: they reported an element of communication, which is specific to a local context and thus not suitable for training outside this very context, for instance Egan et al (), Heidari and Mardani‐Hamooleh () and Anarado, Ezeome, Ofi, Nwaneri, and Ogbolu (); they assessed the effect of a communication tool, for instance Miller et al (), Lipson‐Smith et al () and Cooley et al (); they focused on a singular clinical situation (e.g., fertility preservation) or treatment (e.g., for early stage non‐small cell lung cancer, recurrent ovarian cancer), for instance Elit et al (), Dyer and Quinn (), and Golden, Thomas, Moghanaki, and Slatore (); or they addressed interventions to empower patients, for instance Jones et al (), and Halkett et al ().…”
Section: Methodsmentioning
confidence: 99%